Hospitalidade no ensino a distância na educação superior da cidade de São Paulo: (2010-2014) - REIS, Márcia Cristina dos (2016)
Presented as a form of social inclusion, demand for E-Learning grows exponentially and integrates government targets for expanding access to higher education. This research seeks to understand the role of hospitality in E-Learning in Undergraduate in São Paulo, for the period 2010 to 2014. The overall objective aims to understand the student's interaction with the Virtual Learning Environment (VLE) and the actors involved in the teaching process. To achieve this purpose has the following objectives: a) identify the modalities of distance education courses in higher education institutions in the city of São Paulo in the period 2010-2014; b) describe the platforms used in VLE; c) size the roles of tutors, teachers, engineers and students; d) contextualize the dynamics of the classes according to the type of course. The study methodology relies in carrying out semi-structured interviews, literature review and documentary. The results show that the hospitality and reception are possible in the virtual learning environment by involving integration and interaction of the subjects on the platforms. It highlights the importance of the tutor in this process, as well as attention to the virtual learning environment so that students understand their responsibility and importance in this context.